Investigating the Strategies of Translating Neologisms in Science Magazines from English into Arabic: (A Translational Perspective) - Faris Ahmed Juwair (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
This study investigates the strategies used for translating neologisms from English into Arabic in the context of science magazines. It aims to analyze the frequency of each translation strategy to identify the most commonly applied methods in translating neologisms within this specific genre. The study draws on a model of translation strategies based on Vinay and Darbelnet (1995), Molina and Albir (2002), and Gottlieb (2005). The study uses descriptive and comparative methods and conducts a quantitative analysis of data collected from 10 issues of two science magazines: Scientific American and Nature, along with their Arabic versions. The findings reveal that in Nature, the most frequent strategy is calque, while borrowing appears the least frequent. In Scientific American, calque is also the most common strategy, while amplification is the least frequent one. These results highlight the predominance of calque in translating technical terms, while also indicating the increasing use of borrowing and description when exact equivalents are unavailable. This research may contribute to translation theory and practice, offering insights into how neologisms are handled across languages. Future studies could look into how digital media platforms affect the translation of scientific terms. The role of artificial intelligence in translating neologisms and its impact on translation strategies also warrants investigation. Tracking the evolution of scientific terminology would shed light on how new terms are adopted and integrated into the target language over time. Finaly, the findings in this study could be used by translators, publishers of science magazines, language and translation programs and translator trainers.